2001
DOI: 10.1159/000045996
|View full text |Cite
|
Sign up to set email alerts
|

Salviae Radix Extract Prevents Cisplatin-Induced Acute Renal Failure in Rabbits

Abstract: The present study was carried out to determine if salviae radix extract (SRE) exerts a beneficial effect against cisplatin-induced renal failure in rabbits. Rabbits were pretreated with SRE orally for 7 days, followed by cisplatin injection (5 mg/kg i.p.). Cisplatin injection caused a reduction in GFR, which was accompanied by an increase in serum creatinine levels. The fractional Na+ excretion was increased by cisplatin injection. PAH uptake by renal cortical slices was inhibited by the administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Srivastava et al [49] reported that CPT admnistration results in a significant increase in the activity of calcium-independent nitric oxide synthase (NOS) in rat kidney and liver leading to enhanced NO formation. Thus 6-gingerol might have inhibited inducible nitric oxide synthase and thus reduced the nitrosative stress in rat kidney It has been suggested that ROS may lead to tubular damage in CPT-treated rats [27,45]. Administration of 6-gingerol significantly and dosedependently ameliorated this CPT-induced nitrosative stress.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Srivastava et al [49] reported that CPT admnistration results in a significant increase in the activity of calcium-independent nitric oxide synthase (NOS) in rat kidney and liver leading to enhanced NO formation. Thus 6-gingerol might have inhibited inducible nitric oxide synthase and thus reduced the nitrosative stress in rat kidney It has been suggested that ROS may lead to tubular damage in CPT-treated rats [27,45]. Administration of 6-gingerol significantly and dosedependently ameliorated this CPT-induced nitrosative stress.…”
Section: Discussionmentioning
confidence: 96%
“…Earlier studies had shown that [5]-Gingerol exhibited dose-dependent inhibition of NO production and significant reduction of inducible NO synthase (iNOS) in LPS-stimulated J774.1 cells [32]. Thus 6-gingerol might have inhibited inducible nitric oxide synthase and thus reduced the nitrosative stress in rat kidney It has been suggested that ROS may lead to tubular damage in CPT-treated rats [27,45]. ROS can induce either sub-lethal or lethal cell injury that culminates in either necrosis or apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…[51,52] It has been suggested that ROS may lead to tubular damage in CPT-treated rats. [53,54] ROS can induce either sublethal or lethal cell injury, which culminates in either necrosis or apoptosis. The kidneys of CPT-treated rats showed marked histological alterations, especially in the outer cortex and medullary region of the kidneys, compared with the kidneys of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…11,29) In the previous study, various antioxidant agents showed protective effect against renal injury induced by cisplatin in rats. [30][31][32] In summary, butein, a plant polyphenol, ameliorates renal concentrating ability via up-regulation of renal AQP 2 water channel in rats with cisplatin-induced ARF.…”
Section: Discussionmentioning
confidence: 99%